Multiple Description Watermarking Based on Quantization Index Modulus Modulation - 戴敏倫(Miin-Luen Day); 李素瑛(Suh-Yin Lee); 周義昌(I-Chang Jou) (Journal of Information Science and Engineering, 2007)
In this paper, we study the problem of watermarking for error-prone transmission over unreliable network. We try to integrate an oblivious quantization index modulus modulation (QIMM) watermarking technique into the multiple description coding (MDC) framework and we call it multiple description watermarking technique (MDW). It is known that the balanced MDC encodes a signal source into multiple bitstreams (descriptions) of equal importance and equal data rate. Consider a traditional two-description case in a packet transmission network. The computation for watermark embedding is performed using either description. Once chosen, the corresponding values to be modulated for the other description are assigned with the same values as the just watermarked description. In the detection process, the embedded watermark could be extracted no matter either one or both descriptions are received. That is to say, the watermark is still detectable from MDW even with 50% packet loss. Furthermore, in the case of 50% packet loss, the resulting watermark from MDW is still robust to a variety of image processing attacks, including DCT based compression (JPEG), DWT based compression (JPEG-2000), Gaussian filtering, sharpening and median filtering. The experimental results confirmed the competitive performance and the effectiveness of the proposed scheme.